Launching WordPress- Blogs and Domains (International Journal of Innovative Research in Computer Science & Technology, 2020)
In today’s world, the emphasis is on to move  toward the digital driven economy, businesses, and human  life. This huge movement towards digitization has resulted  in generation of humongous amount of digital content.  Managing this digital content is a challenge in it itself. A  content management system provides way to handle this data  efficiently. CMS are software applications that provide us  the capability for easy management and maintainability of  this digital content. The number of content management  systems have been developed and successfully  productionized such as Word press, Joomla, Cascade Server,  Wix etc. the paper provides an overview of capabilities of  WordPress CMS and various functionalities it offers for  digital content management.
Keywords: Blogs; Domain; SEO; Website; CMS